(untitled) (Research, Society and Development, 2022)
The digestive system encloses a perfect symbiosis between the host and its microbiome. Any disturbance to its dynamics initiates pathological processes, as functional diseases, common to this system. This work was developed so as to understand irritable bowel syndrome, which is a functional disease, and so as to search the literature for the use of the LOW FODMAP diet as a nutritional strategy for the recovery of health in patients with this disease. Through a literature review, in which 3 the considerations and main information related to the topic were selected in articles and books, the FODMAPs, their concepts, characteristics and the food groups that contain them were studied; the way lifestyle and intestinal microbiota act as health modulators; and the functional disease known as irritable bowel syndrome, its pathophysiology, symptoms and possible treatments. Research in which LOW FODMAP dietary therapy was tested in patients with IBS showed a reduction in the disease severity score. Finally, it was concluded that the LOW FODMAP diet contributes to the relief of symptoms related to functional diseases and, especially, irritable bowel syndrome in acute crises.